Endothelial Cell Mechano-Metabolomic Coupling to Disease States in the Lung Microvasculature - Wu, David; Birukov, Konstantin (Frontiers in Bioengineering and Biotechnology, 2019)
Lungs are the most vascular part of humans, accepting the totality of cardiac output in a volume much smaller than the body itself. Due to this cardiac output, the lung microvasculature is subject to mechanical forces including shear stress and cyclic stretch that vary with the cardiac and breathing cycle. Vessels are surrounded by extracellular matrix which dictates the stiffness which endothelial cells also sense and respond to. Shear stress, stiffness, and cyclic stretch are known to influence endothelial cell state. At high shear stress, endothelial cells exhibit cell quiescence marked by low inflammatory markers and high nitric oxide synthesis, whereas at low shear stress, endothelial cells are thought to “activate” into a pro-inflammatory state and have low nitric oxide. Shear stress’ profound effect on vascular phenotype is most apparent in the arterial vasculature and in the pathophysiology of vascular inflammation. To conduct the flow of blood from the right heart, the lung microvasculature must be rigid yet compliant. It turns out that excessive substrate rigidity or stiffness is important in the development of pulmonary hypertension and chronic fibrosing lung diseases via excessive cell proliferation or the endothelial-mesenchymal transition. Recently, a new body of literature has evolved that couples mechanical sensing to endothelial phenotypic changes through metabolic signaling in clinically relevant contexts such as pulmonary hypertension, lung injury syndromes, as well as fibrosis, which is the focus of this review. Stretch, like flow, has profound effect on endothelial phenotype; metabolism studies due to stretch are in their infancy.